Khaled El-Rouayheb and His Contribution to Islamic Philosophy: A Book Literature Review - Moch. Zainul Hasan; Yusuf Hanafi (Saniya Institute, 2024)
The Oxford Handbook of Islamic Philosophy, edited by Khaled El-Rouayheb and Sabine Schmidtke, provides a comprehensive study of Islamic philosophy from the 9th to the 20th century, countering the narrative of stagnation after the 12th century. Utilizing a text- and context-based approach, the volume highlights the contributions of classical philosophers such as Al-Farabi, Avicenna, and Averroes, as well as the innovations of post-classical thinkers like Jalāl al-Dīn al-Dawānī and Mīr Dāmād, who merged logic, theology, and mysticism. It explores the interconnectedness of philosophy, theology, and mystical thought, particularly through the concept of wahdat al-wujud in metaphysics. Additionally, the book examines the impact of colonialism and the relationship between Islamic philosophy and modernity, showcasing figures like Muhammad Abduh and Rashid Rida, who sought to integrate Islamic and Western philosophical traditions. This handbook asserts Islamic philosophy as a vibrant and evolving intellectual legacy, making it an essential resource for scholars, students, and researchers interested in its significance within global philosophical discourse.